PENINGKATAN KEMAMPUAN GUIDING PADA POKDARWIS ALAM PUNCAK LANDEP MELALUI PELATIHAN BERLANDASKAN FALSAFAH TRI HITA KARANA - Kusuma, Ketut Chandra Adinata; Sucita Dartini, Ni Putu Dwi; Ariani, Luh Putu Tuti; Hidayat, Syarif (JURNAL WIDYA LAKSANA, 2021)
The growing number of tourists with special interests, namely sport tourism, especially trekking activities combined with cultural attractions/local wisdom encourages efforts to improve the quality of tour guides. Pokdarwis Alam Puncak Landep was formed to sell service businesses in the field of guidance that do not have the knowledge and understanding of: (1) potential cultural attractions that can be combined with trekking activities, (2) guiding procedures based on the local wisdom, (3) English language skills. To that end, trekking guiding training has been conducted based on the tri hita karana philosophy. The purpose of this training is to improve guiding skills based on the tri hita karana philosophy. The method used is discussion and practice. The results of the training show that there is an increase in knowledge and understanding of combining cultural attractions with trekking activities and practicing guiding procedures combined with using English. Thus, pokdarwis can improve their guiding ability through training based on the tri hita karana philosophy.